Measurement of the fragmentation fraction ratio fs/fd and its dependence on B meson kinematics - Aaij, Roel; Adametz, Aleksandra; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; et al. (Journal of high energy physics, 2013)
The relative production rate of $ B_s^0 $and B0 mesons is determined with the hadronic decays $ B_s^0→ D_s^{-}{π^{+}} $and B0 → D−K+. The measurement uses data corresponding to 1.0 fb−1 of pp collisions at a centre-of-mass energy of $ \sqrt{s}=7 $TeV recorded in the forward region with the LHCb experiment. The ratio of production rates, fs/fd, is measured to be 0.238 ± 0.004 ± 0.015 ± 0.021, where the first uncertainty is statistical, the second systematic, and the third theoretical. This is combined with a previous LHCb measurement to obtain fs/fd = 0.256 ± 0.020. The dependence of fs/fdon the transverse momentum and pseudorapidity of the B meson is determined using the decays $ B_s^0→ D_s^{-}{π^{+}} $and B0 → D−π+. There is evidence for a decrease with increasing transverse momentum, whereas the ratio remains constant as a function of pseudorapidity. In addition, the ratio of branching fractions of the decays B0 → D−K+ and B0 → D−π+ is measured to be 0.0822 ± 0.0011 (stat) ± 0.0025 (syst).
Im Titel sind "s" und "d" in fs/fd tiefgestellt
Gesehen am 19.03.2021
LHCb collaboration: R. Aaij, A. Adametz, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, M. Britsch, A. Di Canto, F. Dordei, C. Färber, M. Fontana, E. Gersabeck, S. Hansmann-Menzemer, T. Hartmann, A. Jaeger, K. Kreplin, G. Krocker, C. Linn, J. Marks, M. Meissner, T. Nikodem, D. Popov, M. Schmelling, P. Seyfert, S. Stahl, J. van Tilburg, U. Uwer, D. Volyanskyy, C. Voß, H. Voss, R. Waldi, S. Wandernoth, D. Wiedner, M. Zavertyaev, A. Zhelezov und weitere 590